Borderlines between Sarcopenia and Mild Late-Onset Muscle Disease - Palmio, Johanna; Udd, Bjarne (Frontiers in Aging Neuroscience, 2014)
Numerous natural or disease-related alterations occur in different tissues of the body with advancing age. Sarcopenia is defined as age-related decrease of muscle mass and strength beginning in mid-adulthood and accelerating in people older than 60 years. Pathophysiology of sarcopenia involves both neural and muscle dependent mechanisms and is enhanced by multiple factors. Aged muscles show loss in fiber number, fiber atrophy, and gradual increase in the number of ragged red fibers and cytochrome c oxidase-negative fibers. Generalized loss of muscle tissue and increased amount of intramuscular fat are seen on muscle imaging. However, the degree of these changes varies greatly between individuals, and the distinction between normal age-related weakening of muscle strength and clinically significant muscle disease is not always obvious. Because some of the genetic myopathies can present at a very old age and be mild in severity, the correct diagnosis is easily missed. We highlight this difficult borderline zone between sarcopenia and muscle disease by two examples: LGMD1D and myotonic dystrophy type 2. Muscle magnetic resonance imaging (MRI) is a useful tool to help differentiate myopathies from sarcopenia and to reach the correct diagnosis also in the elderly.